1980
DOI: 10.1002/tera.1420210315
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenicity of diphenylhydantoin in the New Zealand white rabbit

Abstract: The teratogenic potential of diphenylhydantoin sodium (DPH) was investigated in the rabbit after oral intubation of 0 (Control), 25, 50, 75, 100, and 150 mgkglday from days 7-18 of gestation. Except for reduced maternal weight gains at the two higher dosages, no other obvious pharmacological or toxic effects were noted in treated rabbits.Dose-response-related increases in the resorption and malformation rates were observed. Four litters (one of 14 litters with viable fetuses at 75 mglkglday and three of eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Initially, it was shown that phalangeal hypoplasia was the most common defect seen when phenytoin was administered orally to pregnant rabbits from GD 7 to GD 18 (McClain and Langhoff, 1980). Subsequent studies showed the sensitive period for this defect was GD 14-16 and the digital defects were preceded by edema, dilated blood vessels, hemorrhage, and eventually mesenchymal necrosis (Danielson et al, 1992;Danielsson et al, 1992Danielsson et al, , 1995.…”
Section: Phenytoinmentioning
confidence: 93%
“…Initially, it was shown that phalangeal hypoplasia was the most common defect seen when phenytoin was administered orally to pregnant rabbits from GD 7 to GD 18 (McClain and Langhoff, 1980). Subsequent studies showed the sensitive period for this defect was GD 14-16 and the digital defects were preceded by edema, dilated blood vessels, hemorrhage, and eventually mesenchymal necrosis (Danielson et al, 1992;Danielsson et al, 1992Danielsson et al, , 1995.…”
Section: Phenytoinmentioning
confidence: 93%
“…However, the rats seem to be less susceptible than mice and rabbits for teratogenic action by phenytoin. In the New Zealand White rabbit [45,46] both teratogenicity and fetal growth retardation were observed at the same free concentrations as been related to the same type of effects in human pregnancy [47,48]. Also in mice, teratogenicity has been observed after dosing regimens resulting in clinically relevant maternal concentrations [49][50][51][52].…”
Section: Pharmacological Effectsmentioning
confidence: 96%
“…Common findings in rats, mice and rabbits include fetal growth retardation, CL(P), CP alone, heart defects such as ventricular septal defects, distal digital defects Fig. (3j) and behavioural changes [110,111,113,117,[120][121][122][123][124][125][126]. The similarity of these defects to those seen after exposure to almokalant and dofetilide has been used as additional evidence that these drugs have a common mechanism of teratogenicity [6,91,111,[114][115][116][117].…”
Section: (B) Other Defects In Ratsmentioning
confidence: 97%